Long-Term Consequences of High Titer Neutralizing Antibodies to Interferon-β in Multiple Sclerosis - Dunn, Nicky; Fogdell-Hahn, Anna; Hillert, Jan; Spelman, Tim (Frontiers in Immunology, 2020)
Background: Neutralizing anti-drug antibodies (NAbs) to interferon beta (IFNβ) develop in up to 47% of multiple sclerosis (MS) treated patients inhibiting treatment effect of IFNβ. However, the long-term effect of NAbs remain unknown. Objective: To investigate the long-term consequences of high titre NAbs to IFNβ on disease activity and progression in MS patients. Methods: An observational study including data from all IFNβ treated relapsing remitting MS patients with sufficient NAb test results from the Swedish MS registry. Patients were classified into either confirmed ‘high titre’ or ‘persistent negative’ groups and analysed for differences in disease activity and progression over time. Results: A total of 197 high-titre and 2907 persistent negative patients with 19969.6 follow up years of data were included. High titre NAbs were associated with a higher degree of disease activity at baseline. However, even when accounting for this, the presence of high titre NAbs were also associated with higher disease activity during IFNβ treatment. This persisted even after the next DMT start, suggesting that earlier high titres may partially reduce the effect of later treatments. No difference was found in confirmed disability progression. Conclusion: High titre NAbs to IFNβ are associated with higher disease activity, persisting even after IFNβ discontinuation or switch. These results support use of highly efficient treatment earlier in patients with active disease, to avoid these complications.